ANALISIS PENGARUH STRES KERJA, URAIAN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DINAS PARIWISATA KABUPATEN BOGOR - Edward Efendi Silalahi (Jurnal Cakrawala Ilmiah, 2023)
The role of an organization or institution must have a reliable quality of human resources in playing its role to move the organization or institution in the context of development, of course the main impact of that role is the resulting performance. In the form of performance as one of the goals in exploring the various skills or abilities possessed to be able to run a wheel organization either individual or institution. The purpose of this study is to know and analyze the effect of job stress, job description, job motivation on employee performance. The research method used is survey and explanatory research method to analyze the relationship between variables studied. Analytical test tool used in this research is using multiple regression analysis. The hypothesis was tested by using F test, and t test, the result showed that (1) job description significantly or significantly affect the performance of State Civil Apparatus; (2) job stress significantly or significantly affect the performance of the State Civil Apparatus; (4) job description, job stress, and motivation together (simultaneously) have real or significant effect on the performance of civil servant apparatus employees. There are several implications that can be suggested in this study.